Efeito de variáveis e tipos de secagem na eficiência de secagem de blocos cerâmicos de vedação - Alves Junior, Rubens (2016)
The red ceramic industries have an important role in the construction area, since they are responsible for production of various products used on the market, such as the sealing block. To better serve this market industries are concerned to improve products with environmental responsibility, and reduce the cost in the production steps. Stages that are divided in the preparation of raw materials, extrusion, drying and firing. The drying step is distinguished by being very important for the process, since the product quality is directly related to this step. Thus, this work aims to analyze the influence of the type of drying and its variables, such as temperature, time and ventilation conditions, the efficiency of drying ceramic blocks, aiming to propose a method and more efficient drying condition and low cost operating for red ceramic industry. For that characterized the raw chemical and mineralogical, adapted an electric oven which allowed control of all factors, followed by combinations of factors that the experimental design matrix suggested and finally accompanied to change drying artificial to the natural sun drying with forced convection in the industry study. As a result it can be noted that the raw materials are mainly composed of quartz and feldspar some types. The products made with this raw material when in the drying step is influenced both individual factors such as temperature, drying time and air velocity as the interaction between these factors. The temperature and drying time were the variables of greatest influence on drying efficiency. It was applied to knowledge obtained in the above results, the production line of ceramic industry. Where the average drying efficiency in the ceramic industry, with production of 70,000 daily blocks, was approximately 85%, thus leaving the blocks with a residual moisture content of about 3%, acceptable value for entry into kilns.